Respostas

A melhor resposta!
2014-06-04T16:35:54-03:00
Alguem me ajuda a simplificar essas expressões algébricas, resposta completa!

e) -7a  + 4b - 5 + 3ab - 8ba   ___________8ba é o MESMO que 8ab

- 7a + 4b - 5 + 3ab - 8ba
- 7a + 4b - 5 + 3ab - 8ab=
- 7a + 4b - 5 - 5ab=
-7a + 4b - 5(1 + ab)=

 
f) -w + 8y + 4w - 2 (w + y)
 - w + 8y + 4w - 2w + 2y =
-w + 4w - 2w + 8y + 2y =
-w -2w + 4w + 10y=
   -3w + 4w + 10y=
          1w + 10y
             ou
           w + 10y



g)  - (4x + 5) + 2x + 7(x - 2)
    -4x - 5 + 2x + 7x - 14=
    - 4x +2x + 7x - 5 -14=
    - 4x + 9x - 19=
           + 5x - 19   ou  5x - 19


 
h)6m + 3x - 8m + 5x + 2m + 9

6m - 8m + 2m + 3x + 5x +9=
8m - 8m + 8x + 9 =
    0m + 8x + 9     ou      8x + 9
1 5 1